Beyond a Seat at the Table: Building a Food Coalition Centering Environmental Justice Communities on the North Shore. - Armstrong, O'jhonte.; Garrison, Shadia.; Golden, Olivia.; Menendez, Valeria.; Stewart, Nicholas. (Tufts University. Tisch Library., 2023)
2022 M.A./M.S. in Urban and Environmental Policy and Planning Field Project. Client: Green Beverly.